Influence of Women's Empowerment on Place of Delivery in North Eastern and Western Kenya: A Cross-sectional Analysis of the Kenya Demographic Health Survey - Elizabeth J. Anderson; Joy J. Chebet; Ibitola O. Asaolu; Melanie L. Bell; John Ehiri (Springer, 2020)
Background: Labor and delivery under the supervision of a skilled birth attendant have been shown to promote positive maternal and neonatal outcomes; yet, more than a third of births in Kenya occur outside a health facility. We investigated the association between measures of women's empowerment and health facility-based delivery in Northeastern and Western Kenya. Methods: Analysis of 2014 Kenya Demographic and Health Survey data was conducted. Logistic regression adjusting for demographic factors, contraceptive use, and comprehensive HIV knowledge was used to assess the influence of the validated African Women's Empowerment Index-East (AWEI-E) on the likelihood of women's most recent birth having occurred in a health facility versus at home. Additionally, we explored the mediating effect of contraceptive use on women's empowerment and health facility-based delivery. Results: Compared to respondents with low or moderate empowerment scores, those with high empowerment scores were more likely to have given birth at a health facility [odds ratio (OR) = 1.81; 95% confidence interval (CI) = 1.30, 2.51], although this effect was null in the adjusted model (OR = 0.92, 95% CI = 0.58, 1.45). Respondents with a recent facility birth (n = 372/836) were more likely to have high household-level wealth (40.9% vs 8.6%, p < 0.001) and use a contraceptive method (44.9% vs 27.4%, p < 0.001) than those without facility-based delivery. Current contraceptive use mediated 26.8% of the effect of empowerment on the odds of facility-based delivery. Conclusion: Women's empowerment, and its comprising three domains as measured by the AWEI-E, may be insufficient to overcome barriers to facility-based delivery for women in North Eastern or Western Kenya. High women's empowerment is strongly associated with current contraceptive use, which may inform pregnancy planning and location of delivery. Alternatively, higher empowered women who delivered at a facility may have been offered contraceptives at the time of delivery. Future research targeting these regions should explore culturally acceptable approaches to broadening access to skilled supervision of labor.